(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. In hemodialysis patients, 25-hydroxyvitamin D conversion to active 1,25-dihydroxyvitamin D by the kidneys is very limited. The expression of both vitamin D receptor and 1?-hydroxylase in cells of the immune system and in both osteoblasts and osteoclasts makes it possible that 25-hydroxyvitamin D could play an important role in both inflammation and bone metabolism acting in a autocrine and/or paracrine way in these patients. Materials and Methods. Thirty-three hemodialysis patients not under vitamin D receptor agonist treatment were enrolled into the study. Serum levels of 25-hydroxyvitamin D, C-reactive protein (CRP), interleukin-6 (IL-6), receptor activator of nuclear factor-kappaB ligand (RANKL), and osteoprotegerin, as well as intact parathyroid hormone were assessed by immunoassays. Results. Regarding inflammation, 25-hydroxyvitamin D inversely correlated with both CRP and IL-6. Regarding bone metabolism, 25-hydroxyvitamin D was positively related to osteoprotegerin, but negatively to the RANKL. The latter could be the result of parathyroid hormone suppression by 25-hydroxyvitamin D, since 25-hydroxyvitamin D negatively correlated with parathyroid hormone, which in turn was positively related to RANKL. Conclusions. Serum 25-hydroxyvitamin D is inversely correlated with markers of inflammation and may suppress osteoclastic activity in hemodialysis patients.